ETHNO-DENTISTRY FLORA OF THE EMBERA NATIVE COMMUNITIES FROM ANTIOQUIA’S MEDIO ATRATO REGION - Arango-Arroyave, José Ubeimar; Iságama, María Evalina (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: he forest areas traditionally used and managed by the embera native communities living in the biogeographic Chocó’s tropical rainforests ecosystems contain several plants of dental use. Methods: this study used ethnographic research approaches supported by photographs, botanical samples, forms, field work notes, and taxonomic identification. Results:in the form of an inventory, this work presents the floristic composition and some ethno-botanic notes on the species identified and recognized by the native communities from the Medio Atrato river region which have a medical/cultural value for the oral health of this ethnic group; five species are especially important: three genera of different growing patterns and two families, which are used in preventive oral health. Conclusions: this study allowed concluding that the aforementioned dental practices, and the ancestral knowledge connected to them, are being gradually forgotten, especially by young people but even by the adult members of these ethnic groups.